Herding behaviour in China’s markets and their influences on international markets and trading partners - Chong, Oi Ping (2020)
In its rapid transition to a modern economy, China is undergoing dynamic changes in all of its business sectors and industries, a situation that present features unique to China’s economy. This study focuses on several issues related to the Chinese stock market, and these issues are investigating herding behaviour in four local Chinese markets, which are Shanghai A-share (SHA), Shanghai B-share (SHB), Shenzhen Ashare (SZA) and Shenzhen B-share (SZB). This study used cross-sectional absolute deviation (CSAD) to examine the herding behaviour. First, this study found that the SHA, SHB and SZA showed herding in their markets, but the SZB did not. Second, this study discovered that Hong Kong, Israel, Pakistan and Thailand were herding around the Chinese market. Third, this study discovered that all three categories of total trade with China instead showed the dominant influence of the Chinese market return dispersion. However, the results of this study have shown that the Chinese market did not play a significant role in influencing and causing other local markets or its trading partners to herd around its markets, as did the U.S. market. Thus, the result of this study can be used to reduce the tendency of the formation of herding behaviour.